x + y + z = 3 x 3 + y 3 + z 3 = 3 Let a be the sum of all possible integer values of x .
Let b be the sum of all possible integer values of y .
Let c be the sum of all possible integer values of z .
Find a + b + c .
Details and Assumptions :
All the possible values of x , y , z are to be summed,not only the possible distinct values of x , y , z .For example, if the solutions were ( 1 , 2 , 3 ) and ( 1 , 2 , 4 ) ,then the answer would be 1 + 1 + 2 + 2 + 3 + 4 = 1 3
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Indeed, from ( 3 − x ) ( 3 − y ) ( 3 − z ) = 8 , we have finitely many integers triplets to check. The condition of ( 3 − x ) + ( 3 − y ) + ( 3 − z ) reduces the number of cases further.
Note: Instead of "any one of them even", you mean that "exactly one of them is even".
Great solution! Here is the proof for the first statement: x 3 + y 3 + z 3 − 3 x y z = ( x + y + z ) ( x 2 + y 2 + z 2 − x y − y z − z x ) = ( x + y + z ) ( ( x + y + z ) 2 − 3 ( x y + y z + z x ) ) ⟹ ( x + y + z ) 3 − ( x 3 + y 3 + z 3 ) = 3 ( ( x + y + z ) ( x y + y z + z x ) − x y z ) = 3 ( ( x + y ) ( x y + y z + z x ) + z 2 y + z 2 x ) = 3 ( ( x + y ) ( x y + y z + z x ) + z 2 ( x + y ) ) = 3 ( x + y ) ( z 2 + z x + z y + x y ) = 3 ( x + y ) ( y + z ) ( z + x )
Log in to reply
Here's another approach:
Let
F
(
x
,
y
,
z
)
=
(
x
+
y
+
z
)
3
−
(
x
3
+
y
3
+
z
3
)
.
Observe that
F
(
x
,
−
x
,
z
)
=
(
x
−
x
+
z
)
3
−
(
x
3
−
x
3
+
z
3
)
=
0
.
So
x
+
y
∣
F
(
x
,
y
,
z
)
.
Similarly,
(
x
+
y
)
(
y
+
z
)
(
z
+
x
)
∣
F
(
x
,
y
,
z
)
and so we have
F
(
x
,
y
,
z
)
=
A
(
x
+
y
)
(
y
+
z
)
(
z
+
x
)
.
Finally, from
F
(
1
,
1
,
1
)
=
A
×
2
×
2
×
2
, we conclude that
A
=
3
.
Thanks! I just wrote the conclusion directly and skipped the proof
Problem Loading...
Note Loading...
Set Loading...
Note that ( x + y + z ) 3 − ( x 3 + y 3 + z 3 ) = 3 ( x + y ) ( y + z ) ( z + x ) . Substituting the two given equations together gives
( x + y ) ( y + z ) ( x + z ) = 8 ⇒ ( 3 − z ) ( 3 − y ) ( 3 − x ) = 8 ( 1 )
Again, since ( 3 − x ) + ( 3 − y ) + ( 3 − z ) = 6 , which implies that either all x , y , z are even any one of them even.
From ( 1 ) ,
Case 1: All of them are equal to 2, so x = y = z = 1 .
Case 2: Any one of them is 8 and rest are 1: 3 − x = 8 ⇒ x = − 5 , therefore x = − 5 , y = z = 4 . And because x , y , z are interexchangeable, ( x , y , z ) = ( − 5 , 4 , 4 ) , ( 4 , − 5 , 4 ) , ( 4 , 4 , − 5 ) are all the solutions.
Plutting this all together, we have ( x , y , z ) = ( 1 , 1 , 1 ) , ( − 5 , 4 , 4 ) , ( 4 , − 5 , 4 ) , ( 4 , 4 , − 5 ) are all the solutions satisfying the conditions.
So our answer is 3 ( 1 − 5 + 4 + 4 ) = 1 2 .